2021
DOI: 10.3390/insects12100864
|View full text |Cite
|
Sign up to set email alerts
|

Different Host Plants Distinctly Influence the Feeding Ability of the Brown Citrus Aphid Toxoptera citricida

Abstract: Piercing–sucking insects are important crop pests, and an understanding of their feeding behavior and population development plays a crucial role in studying insect population dynamics and crop resistance. In our study, we examined the probing behavior of the brown citrus aphid, Toxoptera citricida, using electropenetrography and assessed its population development after 8 days on seven host plants: Yuzu, Citrus junos Sieb. ex Tanaka; Rough Lemon, C. jambhiri Lush.; ‘Luofu’ kumquat, Fortunella margarita Swingl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…In cotton, antixenosis is activated after the first aphid attack through the release of plant defense elicitors [44], making the crop less susceptible to aphids. Using electropenetrography, it was shown that the feeding parameters of the brown citrus aphid were different depending on the citrus host species [45]. These results may indicate a potential fitness of aphids dependent on citrus hosts.…”
Section: A Spiraecola and A Gossypii Host Preferencementioning
confidence: 97%
“…In cotton, antixenosis is activated after the first aphid attack through the release of plant defense elicitors [44], making the crop less susceptible to aphids. Using electropenetrography, it was shown that the feeding parameters of the brown citrus aphid were different depending on the citrus host species [45]. These results may indicate a potential fitness of aphids dependent on citrus hosts.…”
Section: A Spiraecola and A Gossypii Host Preferencementioning
confidence: 97%
“…The current methods of managing aphids focus mostly on insecticides [ 10 , 11 ]. In attempting to avoid the negative effects of chemical insecticides, the utilization of resistant tea germplasms to control aphids has emerged as an economical, effective, and environmentally friendly management strategy [ 12 , 13 ]. Unfortunately, few reports regarding the resistance of tea plants to T. aurantii have been published, which are insufficient for screening aphid-resistant tea germplasms.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to their efficiency and accuracy, the electrical penetration graph (EPG) technique and life tables are useful tools for screening insect-resistant germplasm resources to comprehensively analyze the adaptation of piercing–sucking insects to plants [ 12 ]. EPG signals can reflect the location of the stylet in the plant tissue alongside special feeding activities [ 15 , 16 , 17 ] and has been widely used as an advanced technology to examine the feeding behavior of piercing–sucking insects [ 18 ] such as Rhopalosiphum padi (Linnaeus) (Hemiptera: Aphididae) [ 19 ], Toxoptera citricida (Kirkaldy) (Hemiptera: Aphididae) [ 13 ], Myzus persicae (Sulzer) (Hemiptera: Aphididae) [ 20 ], and Bemisia tabaci (Gennadius) (Hemiptera: Aphididae) [ 21 ]. Life table analysis is widely accepted as a powerful tool for researching the dynamics of insect populations.…”
Section: Introductionmentioning
confidence: 99%
“…The level of plant resistance can be reflected by the adaptability of insects towards hosts. Previous studies have shown that insects improve their adaptive ability to host plants primarily through their selection behaviour and feeding habits; therefore, elucidating the feeding behaviour of insects is essential for revealing host resistance mechanisms [14,15]. To overcome the defensive traits of plants, phytophagous insects have evolved different types of mouthparts to adapt to complex environments.…”
Section: Introductionmentioning
confidence: 99%